1998
DOI: 10.1148/radiology.206.1.9423677
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic sarcoma: noninvasive in vivo assessment of tumor necrosis with diffusion-weighted MR imaging.

Abstract: Normalized apparent diffusion coefficients are more accurate in differentiating between viable and necrotic tumor than are T2 relaxation times or relative signal intensity increases on contrast-enhanced images. Signal intensity overlap between viable and necrotic tumor on gadolinium-enhanced images may be caused by the small molecular size of the agent, which permeates the interstitial space freely, thereby also enhancing necrosis. Diffusion-weighted MR imaging depicts differences in diffusion and, ultimately,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
126
1
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 0 publications
1
126
1
8
Order By: Relevance
“…The signal intensity of DWI and the ADC values of the tissue change corresponding to the microstructure characteristics and physiological state of the tissues; these signal intensities have been used in various organs, including musculoskeletal tumors, and many studies have demonstrated the potential for providing information that can contribute to the differentiation between benign and malignant tumors (12)(13)(14)(15)(16). The most important component of signal attenuation on DWI in tumor tissues is the diffusion of water molecules in the extracellular spaces (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal intensity of DWI and the ADC values of the tissue change corresponding to the microstructure characteristics and physiological state of the tissues; these signal intensities have been used in various organs, including musculoskeletal tumors, and many studies have demonstrated the potential for providing information that can contribute to the differentiation between benign and malignant tumors (12)(13)(14)(15)(16). The most important component of signal attenuation on DWI in tumor tissues is the diffusion of water molecules in the extracellular spaces (12).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted MR imaging (DWI) is another method of assessing the functional properties of pathologic tissues and is useful for differentiation between benign and malignant tumors in various fields (8 -11), including the musculoskeletal system (12)(13)(14)(15)(16). DWI permits the quantitative assessment of water diffusion in tissues and therefore is used to measure the apparent diffusion coefficient (ADC), which reflects the mobility of water molecules in the tissues.…”
mentioning
confidence: 99%
“…22,23 It is noteworthy that pathologic responses without any decrease in size were reported even in patients with solid tumors who received cytotoxic chemotherapy. Patients with myxoid liposarcoma who received trabectedin 24,25 and patients with osteosarcoma who received chemotherapy [26][27][28] are examples among sarcomas. We previously demonstrated that Choi criteria adapted to magnetic resonance imaging (MRI) correlated better with pathologic tumor response than RECIST in a series of 38 patients with high-grade soft tissue sarcomas who received preoperative chemotherapy with or without radiation therapy within a prospective phase 3 Italian Sarcoma Group/Spanish Sarcoma Group trial.…”
Section: Introductionmentioning
confidence: 99%
“…DWI enables the visualization of Brownian random motions of water molecules in the extracellular, intracellular, and intravascular spaces [5] . DWI provides information on tissue cellularity and integrity of cell membranes, since the degree of restriction to water diffusion in biological tissues is inversely correlated to these features [6][7][8][9] .…”
Section: Functional Imaging Techniques: Technical Basesmentioning
confidence: 99%
“…DWI enables the visualization of Brownian random motions of water molecules in the extracellular, intracellular, and intravascular spaces [5] . DWI provides information on tissue cellularity and integrity of cell membranes, since the degree of restriction to water diffusion in biological tissues is inversely correlated to these features [6][7][8][9] .Restricted diffusion is present in tissues with narrowed extracellular spaces as a consequence of a high cellular density, which increases the number of hydrophobic cellular membranes, whereas in cystic or necrotic lesions water diffusion is relatively ''free'' [10] . The b value is a technical parameter that regulates the sensitivity of this sequence to water molecules' diffusion.…”
mentioning
confidence: 99%